Correlation of Ferritin and Transferrin Serum with hsCRP and F2-Isoprostane in Metabolic Syndrome - Waode Nurfina; Irawan Yusuf; Mansyur Arif (The Prodia Education and Research Institute (PERI), 2010)
BACKGROUND: The low inflammatory state that accompanies the Metabolic Syndrome (MetS) associates with the overexpression of oxidative stress. Ferritin and Transferrin serum are often used to measure iron status and their concentrations are altered in several metabolic conditions. We hypothesized that concentration of Ferritin and Transferrin serum increase in Metabolic Syndrome (MetS) and correlate with the inflammation and oxidative stress.METHODS: We studied 65 male MetS patients, aged 43.26±7.16 years. Iron metabolism was measured by concentration of Ferritin and Transferrin serums, while inflammatory and oxidative stress by high sensitivity C-reactive Protein (hsCRP) and F2-Isoprostane.RESULTS: Concentration of Ferritin 315.70±188.63 ng/L and Transferrin 2.36±0.31 g/L increased along with increasing components of MetS. Concentration of Ferritin serum had a positive correlation with hsCRP (r=0.220) and F2-Isoprostane (r=0.023).CONCLUSION: Serum concentration of Ferritin increased in the MetS and correlates with hsCRP and F2-Isoprostane.KEYWORDS: metabolic syndrome, ferritin, transferrin, hsCRP, F2-isoprostane